Fiduciary Agreement Implementation in Car Credit Agreement on Financing Institutions of Mandiri Finance of Cirebon Based on Act No. 42 of 199 About Fiduciary - Ardiansyah Alrawi; Agus Triatmoko; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The emergence of various institutions today's economy helped spur the economy of the community. But unfortunately the growth of the economic institutions are not supported by an adequate legal development. The presence of various financial institutions helped bring a major role in economic development of society, especially the poor. These financial institutions emerged as a form of providing funds or capital goods for the public to purchase goods on payment in installments or periodically by consumers. Construction consumer finance based on an agreement with the principle of freedom of contract as legal bases for both parties. In practice financing undertaken by financial institutions poured in the form of a credit agreement. In each of providing credit to their customers finance institutions always face a risk, therefore the customer's business situation and developments to be followed continuously starts the moment the credit is given to the loan. As for giving legal protection to the parties in the process of providing collateral (guarantee), then one of them is with the enactment of Law Fiduciary. Implementation of lending followed by a fiduciary assurance processes at financial institutions in the city of Cirebon most important is the legal effect if the Borrower defaults which are expected to creditors (financial institutions) can be easily exercised fiduciary object. Constraints faced in a fiduciary guarantee is as follows: a. Any cost of making a deed by the Borrower felt heavy, incomplete b. Any requirements of the Borrower to elaborate on the type, brand and quality of the fiduciary object, c. The office registration still limited fiduciary, fiduciary registration e. The office could not provide information on everything about the guarantee with the issuance.Keywords: Financing Institution, Credit Agreements, Fiduciary.